(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
In the last three decades the Porfirio Diaz regime has undergone a profound his- toriographical review. All the constructed ideas that deserved nuances have been reviewed by historians and return to the sources. One such issue is the projection of the country and the ruler Porfirio Diaz in the heyday and success of the dicta- torship. It was understood that the expressions of admiration that Diaz provoke did not deserve much weight. However, according to recent historiography these manifestations are explained in large part because of diplomatic networks that stretched around the world leader in order to project an idea of nation and the world recognition as a creator in the construction of modern Mexico. This projec- tion and the role of diplomats has been studied in relations with Europe and the United States, however, there are no studies on other regions, also important in the national project of Porfirio Diaz. This paper studies how the Mexican government projected in Cuba the Diaz’s image of the Mexican nation and how the diplomatic machinery and other agents associated with the promotional campaign worked, all under the shadow of deceiving.